Effects of salbutamol administration on the morphology and cytoarchitecture of the cerebellum and hippocampus of adult wistar rats - Popoola, AbdulGafar Niyi; Ibrahim, Munirudeen; Ibiyeye, Ruqayyah Yetunde; Faniyi , Ayodeji Amos; Balogun, Musbau Olusesan; Busari , Akeem Olayinka; Garba, Wasiu Olanrewaju; Ogunwale , Kolawole Ayobami; Lawal , Abubakar Zubair; Suleiman , Ibrahim Eleha; Adunmo , Godwin Olawoyin; Nuhu , Abdulrazak (Health & Research Journal, 2025)
Background: Salbutamol is the most preferred and widely used drug for treating bronchial asthma and bronchospasm. Its abuse has however been reported amongst users. Most of the side effects reports on salbutamol are clinical based such as headache, tremor, weakness etc. This study, therefore, investigated the sub-acute effect of oral salbutamol on the general morphology of the cerebellum and hippocampus of adult Wistar rats. Method and Material: Twenty adult Male Wistar rats (125 – 224g) were divided into four groups of five rats each. The control (distilled water); the 20mg/kg salbutamol, the 30mg/kg salbutamol, and the 40mg/kg salbutamol groups. Drugs were administered orally for 21 days. The body weight of each animal was monitored throughout the experiment. On day 22, animals were euthanized, brains excised, fixed in 10% buffered formal-saline, cerebelli and hippocampi were identified and processed with Haematoxylin and Eosin staining techniques. Data were analysed by ANOVA at p≤0.05 level of significance using SPSS and results presented as mean ± SEM Results: Results showed that the animals that received 30mg/kg and 40mg/kg salbutamol had significant weight loss. The cerebellum of the 40mg/kg group showed eroded granule cell layer. Hippocampus also revealed pyknotic cells in the pyramidal cell layers at 30mg/kg and 40mg/kg. Conclusions: This study showed that salbutamol at relatively higher doses caused significant weight loss; degeneration of cerebellum granule cells, which might affect motor coordination; and pyknosis of hippocampal pyramidal cells which may affect learning and memory.